Assessment of the Alterations in Craniovertebral Angle Attributed to Continued Digital Usage as an Etiology for Temporomandibular Joint Disorders in North Indian Population: A Pilot Case-Control Study - Manisha Lakhanpal Sharma; Simran Kaur (Journal of Indian Academy of Oral Medicine and Radiology)
Context: Alterations in the craniovertebral angle (CVA) affect the neutral head position setting in a cascade of changes in the cranio-cervico-mandibular complex. Objectives: This study correlates TMDs with forward head posture (FHP), digital usage, and neck pain. Methods and Material: Seventy subjects of the age group 30-40 were given a standardized questionnaire for TMD assessment followed by a thorough clinical examination of TMJ complex. Thereafter, subjects were divided into two groups. Standardized questionnaires were recorded for neck pain and digital usage. Furthermore, CVA was evaluated by a universal goniometer. Statistical Analysis: One-way ANOVA, unpaired t test, Shapiro–Wilk test, Pearson Coefficient, and Leven’s test were used. Results: In the study group, the prevalence of FHP was 94.2%. There was a significant association between FHP and screen time, neck pain as well as TMDs. However, the association between screen time and TMDs was insignificant. Conclusions: TMDs should be managed using the holistic approach which incorporates a reduction in digital usage, correction of posture, therapeutics for cervicofacial muscles, and TMJ.